MODEL FOR ENTERPRISE INNOVATION ACTIVITY - V. V. Khochenkov (Наука и техника)
The paper gives innovation characteristics. An original model of enterprise innovation activity, which consists of sequential interrelated elements is proposed in the paper. The essence of model elements and their control are considered in the paper.